MODIFICATIONS OF PHONEMES. COMPERATIVE PHONETICS. COMPERATIVE PHONOLOGY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth examination of phonetic and phonological modifications of phonemes, focusing on how these sounds adapt within and across languages. The text explores different types of phoneme modifications, such as assimilation, dissimilation, elision, insertion, and metathesis, illustrating how phonemes change depending on linguistic context and ease of articulation. It then delves into comparative phonetics and comparative phonology, outlining how linguists study and compare sound systems between languages to uncover both universal patterns and language-specific characteristics. The article highlights key components of comparative phonetics—articulatory, acoustic, and perceptual aspects—and discusses comparative phonology’s focus on phonemic inventories, phonotactics, allophonic variations, and suprasegmental features like stress, tone, and intonation. By examining phonetic and phonological differences between languages, the article emphasizes the practical applications of these studies in language teaching, speech technology, historical linguistics, and cultural preservation. This comparative approach provides essential insights into the systemic and functional aspects of sounds, supporting language learners, preserving endangered languages, and enriching our understanding of linguistic diversity and evolution.